SIMULATION AND PRELIMINARY ECONOMIC ANALYSIS OF A COMPLEX OF NUTRIENTS USING CAMISEA GAS - Porlles L., J. (2009)
Peru is in fact a country with important reservoirs of natural gas as Camisea and it opens potential opportunities for gas chemical development. In a mark of a higher enterprise competitiveness, in industry any time is more generalized to account with tools as support for enhanced of process and cost savings. The simulation and optimization of industrial process aided by computer is a powerful alternative. This work has as propose to make the design of a process an economical analysis with preliminary character of an integrated fertilizer complex for several plants: ammonia, nitric acid, ammonia nitrate and urea. The complex to treat the simulation in process where the transformation reactions happen in all steps of the plant, as is the case of nitric acid; it requires a great domain, not alone in the use of a powerful simulator, but a deeper knowledge of reaction kinetics and the thermodynamics of technological process in all steps. The preliminary economical analysis made it indicates that the profitability indexes are low; it reflexes conditions of operation that it has to be improve in another step with more technical information.